Grown-in Defects of InSb Crystals: Models and Computation (Communications in Computational Physics, 2006)
In this paper, we present a model for grown-in point defects inside indium\rantimonide crystals grown by the Czochralski (CZ) technique. Our model is similar to\rthe ones used for silicon crystal, which includes the Fickian diffusion and a recombination mechanism. This type of models is used for the first time to analyze grown-in point\rdefects in indium antimonide crystals. The temperature solution and the advance of the\rmelt-crystal interface, which determines the time-dependent domain of the model, are\rbased on a recently derived perturbation model. We propose a finite difference method\rwhich takes into account the moving interface. We study the effect of thermal flux on\rthe point defect patterns during and at the end of the growth process. Our results show\rthat the concentration of excessive point defects is positively correlated to the heat flux\rin the system.
Keywords: Crystal growth; Czochralski technique; point defects; recombination; thermal flux; finite difference method.